Analysis of Caspase-9 enzyme and Cytochrome C levels in infertile patients - Hashem, Rusul; Abdulfattah, Shaimaa Yousif; Al-nawab, Nabaa; Samawi, Farah Thamer (Iraqi Journal of Science, 2025)
Granulosa cell (GC) apoptosis has impaired oocyte maturation and reduced pregnancy rates. Apoptotic markers have been investigated and are supposed to be reliable predictors of in vitro fertilization (IVF) outcomes. The present research aims to compare caspase-9 and cytochrome C levels in follicular fluid (FF) and their gene   expression (CASP9 and CYCS) in blood in pregnant and non-pregnant women. Further, to investigate if the apoptotic markers can be used in predicting IVF pregnancy outcomes. Two groups of women were recruited: the non-pregnant group (n=40) and the pregnant group (n=40). The CASP9 and CYCS expressions were inspected with the Quantitative Reverse Transcription–polymerase chain reaction (qRT-PCR), whereas their protein levels were examined by enzyme-linked immunosorbent assay (ELISA). A significantly lower gene expression and protein levels of caspase-9 and cytochrome C were observed in pregnant women compared to non-pregnant women. Besides, a significant inverse correlation between pregnancy outcomes and apoptotic markers was detected. It is considered that caspase-9 had the best predictive value of pregnancy outcomes compared to cytochrome C. The findings have indicated that an elevated apoptotic rate of GCs may adversely impact oocyte growth, reduce pregnancy rates, and cause IVF failure.